IRONIA, REPETIÇÃO, SILÊNCIO: O ESTILO DO PENSADOR SUBJETIVO - Sampaio, Sílvia Saviano (Intercâmbio, 2010)
Some aspects of the language theory as proposed by the Danish philosopher Kierkegaard are considered in this paper which rejects the view, as defined by direct communication, that there is adequacy between discourse and its referent, the object. Only the ethically powerful indirect communication, can be thought of , when existence is dealt with. Maieutics, with its power to emphasizing the receptor, is ethical. The addressee, in a way, vanishes,solely to bring out the receptor-to-be.